Pemberdayaan Pengrajin Gula Aren Berbasis Keberlanjutan: Pendampingan Produksi, Branding, dan Digitalisasi di Kampung Naga, Desa Neglasari, Kecamatan Salawu, Kabupaten Tasikmalaya - Deni Danial Kesa; Ari Nurfikri; Debrina Vita Ferezagia; Muhammad Dicka Ma'arief Alyatalatthaf (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2025)
This community service activity was conducted in Kampung Naga, Neglasari Village, Salawu District, Tasikmalaya Regency, known as an indigenous community with strong traditions in processing non-timber forest products, including palm sugar. Palm sugar artisans in this region have great potential to increase the village's economic value, but still face several challenges such as limited production technology, inconsistent quality standards, minimal use of digitalization, and a suboptimal understanding of environmental and economic sustainability. Through qualitative methods based on participatory observation, in-depth interviews, and documentation, this program aims to improve production capacity, efficiency, branding, and digital marketing for artisans. The program results show increased knowledge about production quality, sustainability awareness, digital readiness, and the formation of a more competitive local brand. This article provides a comprehensive overview of the empowerment process, the socio-economic dynamics of artisans, and strategic recommendations for the sustainability of the palm sugar industry in Kampung Naga.